SMART FISH DRYING: Solar-powered Automatic Salted Fish Production System - Arini, Nadine Nova; Bisri, Shahwa Namira; Jaenuri, Jaenuri; Farahdina, Ulya (Faculty of Mathtmatics and Natural Sciences, 2025)
Due to weather instability in recent years, dried fish production in Indonesia has declined, while the quality of the produced dried fish remains low. To address this challenge, the authors introduce